PENGOLAHAN DSM DENGAN INTERFEROMETRI SAR (InSAR) ANTARIKSA UNTUK MEKANISME PEMBANGUNAN BERSIH (MPB) PROTOKOL KYOTO - M. A. Raimadoya; B. H. Trisasongko; D. Shiddiq; D. R. Panuju; R. Maulida (Jurnal Ilmu Tanah dan Lingkungan, 2004)
Capacity development in biomass monitoring is a key action in the implementation of the Clean Development Mechanism of the Kyoto Protocol in developing countries like Indonesia. The objection of this research is to explore the processing of spaceborne InSAR for the construction of the Digital Surface Model (DSM). The research successfully completed the process by using two InSAR pairs: ERS-1 & ERS-2 tandem pass (completed) and ENVISAT repeat pass (coherence only). DSM product, after field validation, will be applied for SAR calibration in relation to biomass and carbon stock estimation. Keywords: CDM, DSM, Kyoto Protocol, spaceborne InSAR